News coverage of Arab revolutions in satellite channels An analytical study of the news bulletins in Al - Tijah satellite channel - علاوي شيماء عبد المجيد; الموسوي حسين علي نور (ALBAHITH ALALAMI, 2015)
The news media material to any means of mass media, and increasingly important in TV; what the associated word and image effects, which do different cover events (political, economic, sports, and social .... etc.) directly from the event site and gather the news and do prepared formulation and arranged within the framework provided by the newsletter, as it requires the viewer to provide the public with information about this news correlated; to achieve the greatest gravity following the shapes and styles and technical fees (Alkraveks) during the submission. What we are witnessing today from technological developments help existing staff to cover the news activity quickly and efficiently prohibitively high, in terms of providing the channel the latest news and developments of events, and receive reports from correspondents, which do not need to cost in coverage (Dropbox, Skype), or in the absence of a private existence reporter hot spots, so it has modern technology has played an influential role in the output of newsletters impacted significantly on the nature of the article submission to the public, accompanied by the ability of workers in the newsroom and Omkanyatem.autamthelt research problem across the main question: Is the direction satellite channel was the ability level of follow-up events through news coverage of continuous form, according to the latest developments in those countries in the newsletter? What is nature successive coverage (rising) of those events?